Efeitos de níveis de cobertura do solo sobre a produtividade e crescimento do feijoeiro irrigado, em sistema de plantio direto - Chieppe Jr., João Baptista; Pereira, Ana Lucia; Stone, Luis Fernando; Moreira, José Aluísio Alves; Klar, Antonio Evaldo [UNESP] (My University, 2007)
The objective of this research was to study the effects of five different treatments of grass (Brachiaria decumbens) straw mulch on common beans (Phaseolus vulgaris L.): 0% (0 t.ha-1), 25% (2,25 t.ha-1), 50% (4,5 t.ha-1), 75% (6,75 t. ha-1) and 100% (9,0 t/ha) designed by randomized blocks, with four replicates. The irrigation was applied when minimum soil water potential were reached about - 30kPa. The water management based on tensiometers and soil water characteristic curve. A microsprinkler irrigation system was used. The experiment was set up at the Experimental Station of Embrapa Rice and Bean (Empresa Brasileira de Pesquisa Agropecuária Arroz e Feijão) at Santo Antonio de Goiás, Brazil, in a Dark - Red Latosol soil. The results showed: the bean yield and his components were not affected by treatments, except grain number/pod,. The mulch increased the water use efficiency and, consequently, decreased the number of irrigations when the mulch reached more than 50% straw mulch. The treatment with 100% of mulching presented the largest leaf area index and dry matter accumulation was not affected by mulching.
Effects of different mulch levels on growth and yield of common beans under no tillage system
Keywords: Braquiária decumbens L; No tillage system; Phaseolus vulgaris; Cultivation; Soil moisture; Sprinkler systems (irrigation); Surface tension; Vegetation; crop yield; dry matter; growth; irrigation system; leaf area index; mulching; soil water potential; water use efficiency; zero tillage; Brachiaria; Urochloa brizantha